2010
DOI: 10.1111/j.1365-2303.2010.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Role and accuracy of rapid on‐site evaluation of CT‐guided fine needle aspiration cytology of lung nodules

Abstract: FNA with ROSE is a safe and useful tool in the diagnostic work-up of lung cancer patients, with no contraindications to its use as the first diagnostic procedure for all patients with peripheral lung lesions. FNA with ROSE should be reconsidered in the guidelines for diagnosing and managing lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 35 publications
(64 reference statements)
1
72
0
Order By: Relevance
“…[6] It may also yield preliminary diagnosis especially in distinguishing between nonneoplastic and neoplastic, if not the precise categorization, for lung lesions. [7] In the present study also preliminary distinction between neoplastic and non-neoplastic was possible on ROSE in a fair number of cases but the final diagnosis was given only after microscopic examination of routine conventional smears [Figure 2]. …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[6] It may also yield preliminary diagnosis especially in distinguishing between nonneoplastic and neoplastic, if not the precise categorization, for lung lesions. [7] In the present study also preliminary distinction between neoplastic and non-neoplastic was possible on ROSE in a fair number of cases but the final diagnosis was given only after microscopic examination of routine conventional smears [Figure 2]. …”
Section: Discussionmentioning
confidence: 75%
“…The close and vigilant appreciation of morphological features according to the set criteria may be highly useful for cytological differentiation of SCC and AdCa. [7] The Papanicolaou (Pap) staining for demonstrating keratinization and observation of acini and three dimensional clusters can be useful in this regard. Previous studies have also observed that Pap staining on cytological smears may highlight even minimal keratinization in comparison to hematoxyline and eosin staining of histological sections for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7] The use of TIC as an adjunct to CNB, not only improves the accuracy of diagnosis[61115] but decreases patient exposure to unnecessary further intervention and discomfort. [711121314151617] Whereas tissue fixation, sectioning and further evaluation may take 24-48 h,[9] TIC would provide the physician with a preliminary diagnosis in mere 1-2 min, enabling for a more rapid initiation of ancillary testing.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Rapid on-site cytologic evaluation informs the operator for need to obtain additional samples and increases diagnostic yield. 10 On average, ROSE improves the per-case adequacy rate by about 12%.…”
Section: Number Of Passesmentioning
confidence: 99%